The complete chloroplast genome sequence of Viscum coloratum (Viscaceae), a semiparasitic medicinal plant. Issue 2 (3rd July 2019) - Wei, Xueping; Guo, Haojie; Che, Peng; Zhang, Bengang; Liu, Haitao; Qi, Yaodong
Abstract: Viscum coloratum (Viscaceae) is a kind of semiparasitic shrub used as medicinal plant. The complete chloroplast (cp) genome of V. coloratum was sequenced and characterized in this study. Length of total cp genome is 128, 744 bp, which is constructed by four typical regions including a large single-copy region (LSC, 73, 684 bp), a small single-copy region (SSC, 8630 bp) and a pair of inverted-repeat regions (IRs, 23, 215 bp). 100 unique genes are predicted including 68 protein-coding genes, 28 tRNA genes and four rRNA genes. Phylogenetic analysis were performed based on 30 shared genes of 12 species in Santalales using maximum likelihood method. The results showed a close relationship between V. coloratum and V. album . The complete cp genome of V. coloratum would provide valuable genetic resources for further study on phylogeny, population genetics and identification in Viscum .